2013
DOI: 10.3758/s13428-013-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Assigning and combining probabilities in single-case studies: A second study

Abstract: The present study builds on a previous proposal for assigning probabilities to the outcomes computed using different primary indicators in single-case studies. These probabilities are obtained by comparing the outcome to previously tabulated reference values, and they reflect the likelihood of the results in the case that no intervention effect is present. In the present study, we explored how well different metrics are translated into p values in the context of simulation data. Furthermore, two published mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Regarding the probability-based approach (MRA), previous evidence suggested that it works well as a translation mechanism between nonoverlap indices (Manolov & Solanas, 2013b). The evidence presented here shows that the similarities extend to standardized difference indices, given the positive and high correlations obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the probability-based approach (MRA), previous evidence suggested that it works well as a translation mechanism between nonoverlap indices (Manolov & Solanas, 2013b). The evidence presented here shows that the similarities extend to standardized difference indices, given the positive and high correlations obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Using simulation methods, Manolov and Solanas (2008) found that PND was the statistic least affected by the presence of autocorrelation when compared to several other single-case effect size measures. Another study by Manolov and Solanas (2013) found that PND’s p values (estimated via simulation) were similarly unaffected by autocorrelation. PND is thus an attractive option for single-case investigators concerned about serial dependency in their data.…”
Section: Assumptions and Limitationsmentioning
confidence: 91%
“…Because its sampling distribution is unknown, it is difficult to perform null hypothesis significance testing (Beretvas & Chung, 2008). PND p values can be estimated with Monte Carlo simulation techniques (Manolov & Solanas, 2013), though few applied researchers may be able or willing to use those computationally advanced methods. Without a defined sampling distribution, PND is a descriptive statistic whereas other effect size measures are inferential (Allison & Gorman, 1994).…”
mentioning
confidence: 99%